2014
DOI: 10.11005/jbm.2014.21.2.143
|View full text |Cite
|
Sign up to set email alerts
|

Physicians' Attitudes to Contemporary Issues on Osteoporosis Management in Korea

Abstract: BackgroundIn management of osteoporosis, several concerns here have been raised. The current issue included the utilization of dual energy X-ray absorptiometry (DXA) and fracture-risk assessment (FRAX), screening of vitamin D deficiency and secondary osteoporosis, and long-term use of bisphosphonate and calcium supplements. There was no study on physicians' attitude on these current issues in Korea. Therefore, we investigated the physicians' attitude on these issues by survey.MethodsWe administered a 30-item q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
23
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 28 publications
(39 reference statements)
3
23
0
Order By: Relevance
“… 6 In addition, our results were similar to those reported in a survey of members of the Korean Society for Bone and Mineral Research, which reported that 99% of the respondents used BMD assessment to help them diagnose and make treatment decisions for their patients. 16 …”
Section: Discussionmentioning
confidence: 99%
“… 6 In addition, our results were similar to those reported in a survey of members of the Korean Society for Bone and Mineral Research, which reported that 99% of the respondents used BMD assessment to help them diagnose and make treatment decisions for their patients. 16 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, in online survey, physicians indicated lack of patients' awareness and restriction by health insurance guideline as the biggest barriers of treatment in Korea. [ 39 ] Second, we could not follow out of town during study periods. This finding might have influence on lower rate of treatment or detection of osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…These factors differed somewhat from a recent survey of US physicians, which showed that, when deciding whether to prescribe bisphosphonates, known risk factors for osteoporotic fracture, such as fracture history, glucocorticoid use, and BMD test scores, were the major considerations for physicians ( Gu et al, 2016 ). However, a previous survey of 100 physician members the Korean Society for Bone and Mineral Research (KSBMR) found that 99% used BMD measurements when making treatment decisions ( Ha et al, 2014 ), and a survey of 114 Australian general practitioners found that rates of both prescription and non-prescription treatment were higher in patients with a history of osteoporotic fracture ( Inderjeeth and Smeath, 2010 ), indicating that doctors in the Asia-Pacific region do consider fracture risk factors when treating their patients. MUSIC OS-AP differed from these previous surveys by focusing specifically on the role of GI events in prescribing decisions.…”
Section: Discussionmentioning
confidence: 99%
“…In the KSBMR survey described above, physicians identified a lack of patient awareness (50%), restrictions by health insurance (47%), and the costs of medication (28%) as the biggest barriers to osteoporosis treatment ( Ha et al, 2014 ). Similarly, a 2010 survey of 247 physician attendees of the first Asian regional osteoporosis meeting of the International Osteoporosis Foundation identified lack of awareness among physicians and patients as the most important barrier to osteoporosis care ( Korthoewer and Chandran, 2012 ).…”
Section: Discussionmentioning
confidence: 99%